The social animal - "Brooks,David" (NewYork)
Includes bibliographical reference and index.
Keywords: MAN WOMAN RELATIONSHIPS-UNITED STATES;SOCIAL MOBILITY-UNITED STATES;SOCIAL STATUS-UNITED STATES;ELITE -UNITED STATES;CHARACTER